The Significance Of Anchoring Bias In Estimating Financial And Economic Indicators: An Experimental Study In Indonesia Setting - Andini, Tassya; Asiri, Marwan (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2016)
Anchoring, in Behavioral Finance terminology, refers to people’s tendency to rely too much on the initial piece of information offered (the "anchor"). Anchoring is widely found in decion making processes, where people make estimates about the likelihood of uncertain events or to predict or recall certain values or outcomes by considering the anchor value and adjusting it upwards or downwards to reach a final estimate. Such adjustments are often insufficient, leaving a cognitive bias in the direction of the initial anchor value (Tversky & Kahneman, 1974). This experimental study was performed in order to detect the presence of anchoring bias in Indonesian setting. Following Kudryavtsev and Cohen (2010)’s procedure, we randomly devided participants into two groups, namely: "control group” (where participants did not receive any anchor value) and "anchoring group” (where participants received some anchoring values). Participants in both groups were instructed to provide their best estimations or answers to questions regarding financial and economic issues. Anchors and the questions were presented with the same order and were expressed in the same scale. Using students of Master of Management Program Universitas Gadjah Mada as respondents, this research was aimed to see whether the answers provided by participants in the anchoring group were affected by the anchor values. Further, we would like to test whether the degree of anchoring biases among female respondents were higher than the biases among male respondents; whether questions related to older topics created higher anchoring biases than the newer ones; and finally, whether anchoring bias among non-finance major students were higher than those among finance students. The results show that anchoring biases were identified among all participants. However, we could not identify higher degree of anchoring bias among female participants than those among male participants. Similarly, we did not identify higher biases in answering questions with older topics than the newer ones. Finally, higher degree of anchoring biases were found among non-finance major students than in finance major students, suggesting the type of knowledge might affect the degree of anchoring bias.